Mindfulness in counselling and psychotherapy: narratives from practitioners in Bhutan and Australia - Percy, Ian David (Curtin University, 2016)
In Western countries therapeutic mindfulness has claimed positive physical benefits and improved mental wellbeing. The Kingdom of Bhutan is addressing social problems through emerging counselling and psychotherapeutic services. A narrative research methodology deconstructed the place of mindfulness in the personal lives and professional practices of six counsellors and psychotherapists in Perth, Western Australia and five counsellors in Bhutan. Their relational and contextual histories led to a reconsideration of the descriptions, purposes and applications of mindfulness.